Numerical Studies on Removal of Nitrogen and Phosphorus by Iron-Oxide Coated Zeolite in PHREEQC - LIANG Xingmei; ZHUANG Luwen; LIN Kairong; WANG Lu; ZHOU Jiangang (Renmin Zhujiang)
This paper conducts the column experiments in the laboratory,simulates the removal of nitrogen and phosphorus in groundwater by natural zeolite and iron-oxide coated zeolite through the geochemical model PHREEQC,respectively,and predicts and compares the long-term removal performance of nitrogen and phosphorus by natural zeolite and iron-oxide coated zeolite.The results show that the iron-oxide coated zeolite is able to remove nitrogen and phosphorus more effectively than natural zeolite with coexistence of the two pollutants.The main mechanisms of nitrogen removal by iron-oxide coated zeolite are ion exchange and physical adsorption,while that of phosphate are hydration reaction of iron oxide.The simulation results also show that the removal of nitrogen and phosphorus by iron-oxide coated zeolite differs from each other a lot under different pH conditions and thicknesses of capping material.